Responding to COVID-19 related mental health impacts among elite athletes - Broughan, J.; Roe, M.; Crowley, T.; Cullen, W. (Irish Journal of Medical Science, 2021)
The COVID-19 pandemic has impacted considerably on elite athletes' performance. In this paper, we aim to examine how the psychosocial effects of COVID-19 may impact on athletes. First, mental health problems are as common among elite athletes as among the general population. Second, the mental health effects of COVID-19 are common in adolescents and young adults. Third, there are recognised gender differences in mental health related help-seeking behaviour. There is emerging evidence that these issues may be exacerbated by the pandemic. While there is little evidence on what interventions may help to address this problem, it is possible that optimising the identification and treatment of mental health problems (in an appropriate and acceptable manner) and promoting team cohesion and interaction may be effective. Addressing this issue is important for all team doctors and healthcare professionals associated with sports teams (both elite and non-elite).